2021
DOI: 10.1002/cam4.4523
|View full text |Cite
|
Sign up to set email alerts
|

Systolic and diastolic blood pressure, prostate cancer risk, treatment, and survival. The PROCA‐life study

Abstract: Background Inflammation has been linked to prostate cancer and hypertension, but it remains equivocal whether elevated blood pressure (BP) influence prostate cancer risk and survival. Method Using Cox regression models, we examined the association between prediagnostic BP and prostate cancer risk among 12,271 men participating in the Prostate Cancer throughout life (PROCA‐life) study. Systolic and diastolic BP were measured. A total of 811 men developed prostate cancer, and followed for additional 7.1 years, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The Prostate Cancer throughout life (PROCA-life) study reported that men (>45 years) with systolic blood pressure > 150 mm Hg had a 35% increased risk of prostate cancer compared with men with systolic blood pressure <130 mm Hg. Prostate cancer patients with high systolic or diastolic blood pressure also had a significantly increased risk of death ( Stikbakke et al, 2022 ). A pooled cohort study recently suggested that elevated blood pressure is unlikely to be an important risk factor for prostate cancer ( Jochems et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Prostate Cancer throughout life (PROCA-life) study reported that men (>45 years) with systolic blood pressure > 150 mm Hg had a 35% increased risk of prostate cancer compared with men with systolic blood pressure <130 mm Hg. Prostate cancer patients with high systolic or diastolic blood pressure also had a significantly increased risk of death ( Stikbakke et al, 2022 ). A pooled cohort study recently suggested that elevated blood pressure is unlikely to be an important risk factor for prostate cancer ( Jochems et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Age at surgery (continuous), CAPRA-S (categorical), BMI (continuous), alcohol habits (categorical), and cholesterol levels (continuous) were included in the final models as covariates. We performed a stratified analysis via systolic blood pressure based on previous observations suggesting that elevated systolic blood pressure is associated with prostate cancer risk [ 44 ]. The proportional hazard assumption was assessed by visually controlling that the log minus log survival curves were parallel.…”
Section: Methodsmentioning
confidence: 99%
“…Note that for senior men, PC is the most common cancer. It is observed in practice that most of the PC patients are affected with cardiovascular disease (CVD) and hypertension [2][3][4][5][6]. Therefore, PC patients are affected with over hypertension risk factors such as systolic blood pressure (SBP) and diastolic blood pressure (DBP) [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed in practice that most of the PC patients are affected with cardiovascular disease (CVD) and hypertension [2][3][4][5][6]. Therefore, PC patients are affected with over hypertension risk factors such as systolic blood pressure (SBP) and diastolic blood pressure (DBP) [6][7][8][9][10][11][12]. The global agestandardized prevalence of over hypertension risk factors such as SBP ≥140 mmHg and DBP ≥90 mmHg in men was estimated as ≥20% in 2015 [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation